Phytosociology and biodiversity patterns of annual wetland communities of Pyriatynskyi National Nature Park (Poltava Oblast, Ukraine) - Kovalenko, Oleksii; Kalista, Mariia (Acta Botanica Croatica, 2019)
The results of a comparative structural analysis of the annual wetland herb vegetation syntaxa (class Isoëto-Nano-Juncetea) of Pyriatynskyi National Nature Park (Poltava Oblast, Ukraine) are presented. The systematic, biomorphological, ecological and geographical structures of syntaxa were studied using cluster, discriminant and factor analysis. The principal conformity of the floristic similarity dendrogram and the previously developed classification scheme were analysed. It was revealed that the leading factor of coenosis development is the soil moisture, while most parameters of these ecotopes are constant. The critical differentiation of Nano-Cyperion and Eleocharition ovatae alliances and the legitimacy of the recognition of the Radiolion linoidis alliance and Polygono recti-Juncetum juzepczukii association as separate syntaxa of the main ranks are emphasized.